Selected problems in the process of designing strategies for sustainable development of municipalities - Sandner, Jan (Studia Ecologiae et Bioethicae, 2019)
The article presents the basic problems of creating sustainable development strategies for municipalities. Municipalities are the basic structures that are responsible for shaping local development. Correct strategic planning can correctly orient the development of basic socio-economic processes of a given community. The article presents the role of natural resources in this process. Describes the possible methods of implementing and valorising environmental resources.